2015
DOI: 10.1016/j.bios.2014.11.036
|View full text |Cite
|
Sign up to set email alerts
|

How does fluorescent labeling affect the binding kinetics of proteins with intact cells?

Abstract: Fluorescent labeling is a mainstream technology for detecting molecular binding. Despite the importance, few studies have been devoted to quantitatively examine the effect of labeling on the molecular binding processes. Here we present a quantitative study on the binding kinetics of fluorescent-labeled and un-labeled molecules (lectin proteins) with glycoproteins on the membrane of cells using surface plasmon resonance imaging (SPRi) technique. The study shows that fluorescent labeling has a significant influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 22 publications
1
58
0
Order By: Relevance
“…6C) show that interactions between lipids and full-length M1 might involve residues belonging to N-terminal domain (and therefore to M1-N as well) that possess aliphatic amines able to react with the succinimidyl ester group in the fluorescent label, such as Gln75, Gln81, Arg76 and Arg77. Notably, a recent SPR study has shown that labeling of wheat germ agglutinin with fluorescent groups reduces significantly binding affinity of this lectin [62]. Unfortunately, we could not study binding of labeled M1-N via SPR since, due to the rather low labeling efficiency (see above), SPR would report essentially on the non-labeled protein fraction.…”
Section: Discussionmentioning
confidence: 96%
“…6C) show that interactions between lipids and full-length M1 might involve residues belonging to N-terminal domain (and therefore to M1-N as well) that possess aliphatic amines able to react with the succinimidyl ester group in the fluorescent label, such as Gln75, Gln81, Arg76 and Arg77. Notably, a recent SPR study has shown that labeling of wheat germ agglutinin with fluorescent groups reduces significantly binding affinity of this lectin [62]. Unfortunately, we could not study binding of labeled M1-N via SPR since, due to the rather low labeling efficiency (see above), SPR would report essentially on the non-labeled protein fraction.…”
Section: Discussionmentioning
confidence: 96%
“…Nonnegative matrix factorisation applied to the imaginary part and the average real part of the susceptibility with an additional concentration constraint (FSC 3 method) was used to obtain susceptibility spectra of independently varying chemical components and their volume concentrations. The FSC 3 is unsupervised and thus does not require prior knowledge of the spectra of chemical components and instead uses random initial guesses. A detailed overview of the data analysis procedure is described in ref 15.…”
Section: Discussionmentioning
confidence: 99%
“…Whilst fluorescence microscopy remains the most widely used optical tool for imaging cellular components with high spatial resolution, with technologies such as super-resolution light microscopy achieving resolution in the submicrometre range, the technology is limited by a necessity for exogenous label incorporation to enable chemical specificity 1 . The majority of these fluorescent labels share a similar molecular weight with many small biological molecules, consequently affecting their physical and chemical properties [2][3][4][5] . Fluorophores are also susceptible to photobleaching with prolonged excitation and cells can become damaged by light at the necessary wavelengths, leading to difficulties in observing samples over longer timescales 6 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this technique requires the labeling of the molecules of interest that can be a drawback in certain investigations. In some cases, it might not be possible to attach a label, or the label might affect the kinetics of the molecules under study.…”
Section: Introductionmentioning
confidence: 99%